PENGARUH HARGA, KUALITAS PRODUK, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SERABI BANDUNG “PELANGI” DI MOJOKERTO - Ichwan Bagus Airlangga; Jamianto Jamianto; Ali Mahsun (Yos Soedarso Economic Journal (YEJ), 2020)
This study aims to analyze the effect of price, product quality, location and promotion on purchasing decisions. The research method used is a quantitative method. This study uses purposive sampling. The sample in this study amounted to 50 respondents. Data collection instrument using a questionnaire. The dependent variable is the purchase decision variable and the independent variable is price, product quality, location and promotion, namely price, product quality, location and promotion on the purchasing decision of Serabi Bandung "Pelangi" in Mojokerto. The data analysis method used is multiple linear regression. All statements are valid, reliable and normal. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.821 or 82.1%. The independent variable can explain the dependent variable. From the research, it shows that price has a significant effect on the purchasing decision of "Rainbow" Bandung Pancakes in Mojokerto. This is proven by tcount being greater than ttable (2.523 > 2.014). And product quality has a significant effect on the purchasing decision of Serabi Bandung "Rainbow" in Mojokerto. This is evidenced by tcount being greater than ttable (5.120 > 2.014). Meanwhile, location does not significantly influence the purchasing decision of Serabi Bandung "Rainbow" in Mojokerto. This is evidenced by tcount which is smaller than ttable (-1.035 <2.014). And so does the promotion does not significantly influence the purchase decision "Rainbow" Serabi Bandung in Mojokerto. This is evidenced by tcount which is smaller than ttable (0.389 <2.014). While the results of the simultaneous test of price, product quality, location and promotion variables have a significant effect of fcount 51.639 > ftable 2.58 on purchasing decisions. This shows that, the better the price, product quality, location and promotion given, it will increase the buying decision of Serabi Bandung "Pelangi" in Mojokerto. Keywords: Price, Product Quality, Location, Promotion, Purchase Decision